Penentuan Jumlah Tenaga Kerja untuk Memenuhi Target Produksi Plat Ring Kaki Sofa (Studi Kasus : UD. Arthomoro) - Haykal, Fikri; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
UD.Arthomoro is a company engaged in manufacturing metal or iron plate processing, located at JL Nusa Indah No. 21 Kureksari, Waru, Sidoarjo. The focus of this research is on the foot ring plate of the sofa/spring bed. This research was conducted to analyze whether the paper production section at PM One experienced a shortage of workers. In this context, a labor shortage can be interpreted as meaning that UD.ARTHOMORO has not found the ideal number of workers to achieve optimal production efficiency. To overcome this problem, the research used the Work Load Analysis (WLA) method. The research results show that paper production at PM one reached 9000 PCS, with a manufacturing time of around 22.99 minutes per 30pcs. WLA's analysis concluded that to achieve that level of production, 17 workers were needed. However, in reality, there are only 9 workers working in that section. Therefore, an additional 8 workers are needed so that production can run optimally. One of the proposed solutions is to provide overtime hours to the 9 existing workers, without increasing the number of workers. The calculation results show that the costs incurred by the company for overtime hours are lower than adding new workers. Therefore, from a financial perspective, providing overtime hours to existing workers is a more efficient option. One of the proposed solutions is to provide overtime hours to the 9 existing workers, without increasing the number of workers. The calculation results show that the costs incurred by the company for overtime hours are lower than adding new workers. Therefore, from a financial perspective, providing overtime hours to existing workers is a more efficient option. However, companies need to consider other aspects such as productivity and worker fatigue due to prolonged overtime hours. Even though it is financially more profitable, worker fatigue can have a negative impact on production quality and worker welfare. Therefore, companies must make decisions wisely, considering various related factors, including aspects of employee welfare.